Tissue specific expression of the human alpha-1-antitrypsin gene in transgenic mice. - Sifers, R N (1987)
Normal and mutant human alpha-1-antitrypsin genes were cloned from a PiMZ heterozygous individual. Nucleotide sequence comparison demonstrated a T to C transition in exon III and an G to A transition in exon V of the PiZ gene. A 14.4 kb DNA fragment containing the entire PiM gene plus 2 kb of 5' and 3' flanking genomic DNA sequences was introduced into the germ line of mice and five F0 transgenic lines were established. Transgenic F1 progeny from F0 parents exhibited high levels of human alpha-1-antitrypsin protein in their plasma. The human gene was expressed primarily in liver of the transgenic mice as it is in man. However, expression of the human alpha-1-antitrypsin gene was also observed in kidneys of the transgenic mice, which led to the observation that the endogenous mouse gene is also expressed in the kidney. These data indicate that cis-acting elements within or proximal to the human alpha-1-antitrypsin gene are able to direct its in vivo transcription with a high degree of tissue specificity.